From Earth to Mars: a perspective on exploiting biomineralization for Martian construction - Khoshtinat, Shiva; Long-Fox, Jared; Hosseini, Seyed Mohammad Javad (Frontiers in Microbiology, 2025)
The future of Mars colonization hinges on the ability to construct durable infrastructure using locally available resources. Given the high cost and logistical complexity of transporting construction materials to Mars, the development of autonomous in situ resource utilization (ISRU) technologies is imperative. This perspective article explores the potential of biomineralization as a low-energy, sustainable alternative to conventional construction methods, such as Portland cement and thermal sintering approaches proposed for lunar applications, which are often energy-intensive and constrained by material specificity. Following an assessment of the chemical composition of Martian regolith, its suitability as a substrate for various biomineralization pathways, particularly those aligned with ISRU constraints, is evaluated. Special emphasis is placed on identifying biological pathways that are not only metabolically compatible with Martian geochemistry but can also function as a co-culture, mutually supporting each other’s survival and activity under Martian environmental stresses. The most promising microbial consortia for biocementation are proposed for future extraterrestrial construction applications. The integration of robotics and automation in biocementation-based additive manufacturing using Martian regolith as a construction feedstock is discussed. Advanced robotic systems equipped with multi-axis extrusion nozzles, sensor suites, and real-time flow control are proposed for the construction of structurally resilient geometries on Mars. As a flexible, scalable, and ISRU-compatible technology, biocementation holds promise not only for infrastructure construction but also for integrated resource cycles, producing oxygen and ammonia as byproducts. Biocementation-based ISRU construction represents a synergistic pathway toward sustainable human presence on Mars, enabling robotic fabrication of critical infrastructure from locally available materials.